Productivy of cotton (Gossypium hirsutum) as influenced by organic and inorganic sources of nitrogen - DAS, ANUP; GAUTAM, M; GAUTAM, R C; SHIVAY, Y S (The Indian Journal of Agricultural Sciences, 2011)
An experiment consisting of 11 treatments was conducted at the Indian ,Agricultural Research Institute, New Delhi, during 2001 and 2002 to assess the effects of different nitrogen sources on cotton (Gossypium hirsutum L.) productivity. The results indicated considerable increase in yield attributes, seed cotton yield (2.33 tonnes/ha) and NPK uptake by cotton with the combined application of 30 kg Nand FYM@12 tonnes/ha along with Azotobacter(M4), but remained on a par with combined application of 30 kg N/ha and FYM @12 tonnes/ha, as well as single application of 60 kg N/ha. Application of30 kg N/ha Azotobacter (M4orW5)’ recorded yield attributes, seed cotton yield and nutrient uptake on ,a par with 60 kg Nlha alone. Different nitrogen management practices did not exert any significant effect on various quality parameters ofcotton, viz ginning percentage, lint index, fibre length, bundle strength and fibre fineness etc. Application of FYM could either maintain or improve the soil fertility status as was evident by the post harvest soil available NPK status, especially when fertilizer N was also added. It was concluded that application of FYM@12 tonnes/ha could save fertilizer N to the tune of 30 kg/ha and thereby economize fertilizer use in cotton cultivation.